(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2024)
This paper aims to compare the concepts of prophets and apostles contained in hadith from Sunni and Shi’a perspectives. The religion of Islam embraced by billions of people around the world has two schools called Sunni and Shi’ah. Sunnis and Shi’a believe that the main source of Islamic teachings is the Qur’an and hadith, but in the Shi’a school has its own collection of hadith that is different from the Sunni school. The main problem raised is how the concept of prophets and apostles in the hadith. The method used is the descriptive method of analysis with a qualitative approach and library research, namely analyzing hadith texts from the hadith books of Sunni and Shi’a. Data sources are collected from primary and secondary data sources. Primary data sources are collected from the book of saheeh Bukhari for the Sunni view and the books of Ushul al-Kafi and Bihar al-Anwar for the Shi’a view. Meanwhile, secondary data sources come from books, literature and relevant previous research. The results of the study show that from the two ideas agree on the role of the prophet and the messenger, trust the number of prophets and recognize the prophet Muhammad Saw as the last prophet, but there are also differences in the definition of the prophet and the messenger, as well as the view on the position of the imams who are equal to the Prophet in certain aspects.